Use of Intranasal Splints to Prevent Post Operative Nasal Synechia Formation (Medical Forum Monthly, 2024)
Objective: This study was conducted to see the effect of intranasal splints in preventing post operative nasal synechia in patients who underwent intranasal surgery. Study Design: Observational and descriptive study.Place & duration of study: This study was carried out at the Department of ENT, Islam Teaching Hospital, affiliated to Islam Medical College, Pasrur road, Sialkot, Pakistan: from June 2007 to December 2013.Materials and Methods: Fifty four patients coming to Islam Teaching Hospital Sialkot from September 2012 to December 2013 were selected. Intransal splints were used in all patients after the intransal surgery. Nasal pack was removed on 1st or second post operative day. Intranasal splints were removed on 7th post operative day in the clinic without anesthesia. Follow up was done on 7th post operative day, 2 weeks and then monthly for 3 months.Results: In this study there were 36 cases (66.7 %) were among male patients and 18 cases (33.3 %) were among female patients. The Maximum age of the patients in this study was 45 years and minimum age of the patients was 9 years and mean age was 25.70. There were 2 cases (3.7 %) of septal abscess drainage, 2 cases (3.7 %) of septal hematoma drainage, 8 cases (14.8 %) of Septoplasty, 2 cases (3.7 %) septoplasty and bilateral partial inferior turbinectomy, 6 cases (11.1 %) of septoplasty plus bilateral partial inferior turbinectomy, 4 cases (7.4 %) of septoplasty plus left inferior turbinectomy & septoplasty plus manipulation of fractured nasal bones, 2 cases (3.7 %) of septoplasty plus nasal cauterization, 20 cases (37 %) of septoplasty plus right inferior turbinectomy, 2 cases (3.7 %) of septoplasty plus right inferior turbinectomy plus trimming of right middle turbinate & septoplasty plus right intranasal polypectomy. There were 10 patients (18.5 %) in which the nasal pack was removed on 1st day and 44 patients (81.5 %) in which nasal pack was removed on 2nd day.Conclusion: Intranasal splints made of intravenous fluid bottle soft plastic are well tolerated and they were effective in preventing nasal synechia formation.